Predictors of timely diagnostic follow-up after an abnormal Pap test among Hispanic women seeking care in El Paso, Texas - Thelma Carrillo; Jane R. Montealegre; Christina G. Bracamontes; Michael E. Scheurer; Michele Follen; Zuber D. Mulla (BMC, 2021)
Abstract Background Diagnostic follow-up of women with an abnormal Pap test is necessary to resolve the risk developing cervical cancer. The purpose of this study is to describe patient characteristics associated with timely receipt of a diagnostic colposcopy after an abnormal Pap test among Hispanic women in El Paso, a Texas-Mexico border city. Methods We conducted a retrospective chart review of Hispanic patients seen at an academic colposcopy clinic following an abnormal Pap test. An optimal diagnostic interval to colposcopy was based on a National Breast and Cervical Cancer Early Detection Program (NBCCEDP) quality indicator and was defined as receipt of colposcopy within 90 days or less from the date of an abnormal Pap test. Risk ratios (RR) were calculated by building a generalized linear model fit using a Poisson distribution, log link, and robust variance. Results Overall, 177 of the 270 women (65.6%) received follow-up within an optimal diagnostic interval. After adjusting for other variables in the model, women who were 30 years of age or older were 32% more likely to have an optimal interval than younger women (adjusted RR = 1.32, P < 0.01). High school graduates were less likely than more educated women to have an optimal interval (adjusted RR = 0.68, P < 0.01). Participation in the NBCCEDP was not associated with receipt of follow-up within an optimal diagnostic interval. Conclusions Compared with women with greater educational attainment, high school graduates were less likely to receive follow-up within an optimal diagnostic interval, as were younger (≤ 30 years) women compared with older women. Participation in the NBCCEDP was not associated with receipt of care within an optimal diagnostic interval.